Relating Metopic Craniosynostosis Severity to Intracranial Pressure. Issue 8 (22nd November 2022) - Blum, Jessica D.; Beiriger, Justin; Kalmar, Christopher; Avery, Robert A.; Lang, Shih-Shan; Villavisanis, Dillan F.; Cheung, Liana; Cho, Daniel Y.; Tao, Wenzheng; Whitaker, Ross; Bartlett, Scott P.; Taylor, Jesse A.; et al.
Abstract : Purpose: A subset of patients with metopic craniosynostosis are noted to have elevated intracranial pressure (ICP). However, it is not known if the propensity for elevated ICP is influenced by the severity of metopic cranial dysmorphology. Methods: Children with nonsyndromic single-suture metopic synostosis were prospectively enrolled and underwent optical coherence tomography to measure optic nerve head morphology. Preoperative head computed tomography scans were assessed for endocranial bifrontal angle as well as scaled metopic synostosis severity score (MSS) and cranial morphology deviation score determined by CranioRate, an automated severity classifier. Results: Forty-seven subjects were enrolled between 2014 and 2019, at an average age of 8.5 months at preoperative computed tomography and 11.8 months at index procedure. Fourteen patients (29.7%) had elevated optical coherence tomography parameters suggestive of elevated ICP at the time of surgery. Ten patients (21.3%) had been diagnosed with developmental delay, eight of whom demonstrated elevated ICP. There were no significant associations between measures of metopic severity and ICP. Metopic synostosis severity score and endocranial bifrontal angle were inversely correlated, as expected ( r =−0.545, P <0.001). A negative correlation was noted between MSS and formally diagnosed developmental delay ( r =−0.387, P =0.008). Likewise, negative correlations between age at procedure and both MSS and cranial morphology deviation was observed ( r =−0.573, P <0.001 and r =−0.312, P =0.025, respectively). Conclusions: Increased metopic severity was not associated with elevated ICP at the time of surgery. Patients who underwent later surgical correction showed milder phenotypic dysmorphology with an increased incidence of developmental delay.